Shape optimization for interface identification in nonlocal models - Matthias Schuster; Christian Vollmann; Volker Schulz (Computational Optimization and Applications, 2024)
Shape optimization methods have been proven useful for identifying interfaces in models governed by partial differential equations. Here we consider a class of shape optimization problems constrained by nonlocal equations which involve interface–dependent kernels. We derive a novel shape derivative associated to the nonlocal system model and solve the problem by established numerical techniques. The code for obtaining the results in this paper is published at ( https://github.com/schustermatthias/nlshape ).
Keywords: 510; Shape optimization; Nonlocal convection–diffusion; Finite element method; Interface identification